2018
DOI: 10.1021/acs.jpcb.8b07525
|View full text |Cite
|
Sign up to set email alerts
|

Does Ionic Screening Lower Activation Barriers for Conformational Transitions in Proteins?

Abstract: In this work, we investigated the kinetics of binding of hen egg-white lysozyme with tri-N-acetylglucosamine in aqueous solutions, at two values of pH, 3.2 and 11, as a function of ionic strength, by a stopped-flow method with tryptophyl fluorescence observation of the transients. We analyzed registered reaction progress curves by employing numerical integration of appropriate chemical master equations. We discriminated between several binding models and established that the process observed in experiments fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…Analysis of these two particular sets of progress curves with the DynaFit 39,40 program and the reaction model represented by eq 1 gives the diffusional encounter rate constant for formation of the encounter complex, 2.59 ± 0.04 and 2.77 ± 0.02 μM −1 s −1 for the mutant and wild-type, respectively. The result obtained for the wild-type lysozyme is close to the average value obtained in our previous study, 63 2.98 ± 0.08 μM −1 s −1 , at pH 3.2 and 20 °C, in the glycine−HCl buffer without addition of KCl.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Analysis of these two particular sets of progress curves with the DynaFit 39,40 program and the reaction model represented by eq 1 gives the diffusional encounter rate constant for formation of the encounter complex, 2.59 ± 0.04 and 2.77 ± 0.02 μM −1 s −1 for the mutant and wild-type, respectively. The result obtained for the wild-type lysozyme is close to the average value obtained in our previous study, 63 2.98 ± 0.08 μM −1 s −1 , at pH 3.2 and 20 °C, in the glycine−HCl buffer without addition of KCl.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…It is most probably related to the relatively substantial standard error of our results. The results for the wild-type lysozyme agree very well with the results obtained in our previous work for slightly lower pH (3.2) and twice larger concentration of the protein.…”
Section: Resultssupporting
confidence: 90%
“…Specific ions effect also known as the Hofmeister effect deals with the effect of ions on biological systems at high (> 0.3 M) salt concentrations. It has been shown that the specific ions effect influence numerous fundamental properties of proteins such as conformational equilibrium between different states of proteins [1][2][3][4], protein dynamics/flexibility [5][6][7][8][9], protein stability [10][11][12][13][14], and formation of amorphous aggregates and ordered fibrils [15][16][17]. Salts modulation of equilibrium between conformational states by decreasing a barrier between them inevitably increases the rate of interconversion (dynamics) as well as the accessibility of these two states (flexibility) [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the specific ions effect influence numerous fundamental properties of proteins such as conformational equilibrium between different states of proteins [1][2][3][4], protein dynamics/flexibility [5][6][7][8][9], protein stability [10][11][12][13][14], and formation of amorphous aggregates and ordered fibrils [15][16][17]. Salts modulation of equilibrium between conformational states by decreasing a barrier between them inevitably increases the rate of interconversion (dynamics) as well as the accessibility of these two states (flexibility) [3,8]. As it has been shown previously, modification of the energy landscape of the active site affects substrate binding and rate of the substrate transformation by the enzyme [13,14,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%